Multiple syphilitic chancre on the vulva and on both breasts: case report - Ledesma, Mauricio; Orsini, Adrián (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Multiple syphilitic chancre is not frequent in the immunocompetent patient. On the other hand, extragenital lesions are more common in the mouth and anus, and it is rare to find them in the breast. We report the case of an 18 year-old patient who attended the consultation with three syphilitic chancres: one on the vulva and one on each areola.